Proceso de ASC - TRANSMISION DE DATOS DESDE UN GLOBO CAUTIVO A UNA ESTACION DE TIERRA (2021)
With this project, the use of the long-range ground station (500 km), located at the EAFIT Llanogrande headquarters, was proposed to receive and process the information sent from a captive balloon that has a sensor system for different variables, which It will be located at different points of the University's Llanogrande headquarters, taking advantage of its large area. Both the operation of the ground station and the captive balloon with its sensor system are in the completion stage within the framework of previous projects in recent years of the Applied Electromagnetism Hotbed (SEMA). Taking advantage of the reception range capacity of the ground station, the aim is to integrate both projects to explore technologies for transmitting and receiving information from earth observation systems.